Aboriginal religions in Australia: an anthology of recent writings - Charlesworth, M. J.; Dussart, Françoise; Morphy, Howard (Vitality of indigenous religions series, 2005)
Revaluations -- Religious business -- Sacred places -- Art and religion -- Different dreamings -- Religions and law -- Religious exchanges